Supervisi Pendidikan Humanis: Solusi Strategis dalam Mengembangkan Kompetensi Guru: Supervisi Pendidikan Humanis: Solusi Strategis dalam Mengembangkan Kompetensi Guru - Riabudiastuti Astuti; Yari Dwikurnaningsih; Herry Sanoto (Pendidikan Dasar dan Manajemen Pendidikan, 2026)
Teacher professionalism remains a major challenge in improving educational quality, particularly regarding inadequate teaching administration, low self-development initiative, and the perception of supervision as merely administrative control. This study aims to analyze the implementation of humanistic educational supervision as a strategic solution to enhance teachers’ competencies. A qualitative descriptive approach was employed, using oral interviews and direct observations to collect data. The data were analyzed through reduction, categorization, and thematic interpretation. The findings reveal that many teachers rarely prepare teaching documents independently, often copy administrative materials, and only complete tasks when sudden inspections occur. Professional development tends to be financially driven rather than quality-oriented, resulting in low participation in workshops and school programs. Task responsibility and assessment preparation are also poorly executed. These conditions indicate that traditional inspection-based supervision fails to improve teacher performance. Conversely, humanistic supervision emphasizing mentoring, reflective dialogue, and collaborative guidance fosters greater responsibility, intrinsic motivation, and continuous professional growth. Therefore, transforming supervision from a controlling mechanism into supportive coaching is essential for sustainable teacher competence